Effect of Different Levels of Surface Application of Sorghum Residue under Minimum Tillage on Crop Yields and Sustainable Yield Index of Sorghum (Sorghum bicolor (L.) Moench) and Cowpea (Vigna unguiculata (L.) Walp) and Nutrient Status in Rainfed Alfisol Soils. Issue 2 (19th January 2022) - Sharma, K.L.; Lal, Munna; Sammi Reddy, K.; Indoria, A.K.; Chandra Sekhar, Ch.; Srinivas, K.; Prabhakar, M.; Singh, V. K.; , Brajendra; Gayatri, D. L. A.
ABSTRACT: In order to assess the effect of surface application of sorghum residue under minimum tillage on crop yields sustainable yield index (SYI), agronomic efficiency (AE), and soil fertility in sorghum-cowpea system, a long-term study was conducted in rainfed Alfisols. The results of the study revealed that surface residue application increased the crop yields significantly over the control ie no residue application, with SYI ranging from 0.52 in no residue application (T1) to 0.70 in residue application @ 4 tha −1 (T3) for sorghum and from 0.01 in residue application @ 2 tha −1 (T2) to 0.08 in residue application @ 6 tha −1 (T4) in cowpea. The AE of the recommended N applied varied from 24.42 to 31.60 in case of sorghum and 10.38 to 13.40 kg grain kg −1 N in cowpea, respectively. The content of soil organic carbon (SOC) after 12 years of experiment ranged from 4.47 to 6.62 g kg −1 and decreased with the soil depth. The level of mean available nitrogen (N), phosphorus (P), and potassium (K) in soil were 154.07-403.45, 5.28–14.07, and 118.17–268.17 kgha −1, while the total N, P, and K varied from 330.0 to 1033.0, 194.9 to 395.7, and 13355 to 22133 mg kg −1, respectively. The available zinc (Zn), manganese (Mn), iron (Fe), and copper (Cu) in soil ranged from 0.08 to 0.98, 9.10 to 38.81, 1.85 to 10.58, and 0.75 to 1.64 mg kg −1, while the total Zn, Mn, Fe and Cu ranged from 21.75 to 86.58, 343.0 to 877.83, 15202 to 33646, and 24.17 to 82.00 mg kg −1, respectively. When the crop yields were regressed with organic carbon (OC) and total and available soil nutrients, the coefficients of multiple determinations (R 2 ) were 0.959 and 0.970 ( P = .05 and P = .01) for available soil nutrients and 0.944 and 0.827, for total nutrients, respectively. The OC, available N and Zn contents and total K and Mn have positively influenced yields of both the crops in these soils.